Emulating a randomized clinical trial with real-world data to evaluate the effect of antidepressant use in PTSD patients with high suicide risk - Oshin Miranda; Xiguang Qi; M. Daniel Brannock; Ryan Whitworth; Thomas Kosten; Neal David Ryan; Gretchen L. Haas; Gretchen L. Haas; Gretchen L. Haas; Levent Kirisci; LiRong Wang (Frontiers in Psychiatry)
IntroductionPost-Traumatic Stress Disorder (PTSD) entails behavioral changes with increased risk of suicide, and there is no consensus on the preferred antidepressants for treatment of those PTSD patients who are at elevated risk for suicide.MethodsWe conducted a clinical trial emulation study comparing suicide-related events (SREs) among those patients’ initiating antidepressants within 60 days after a qualifying SRE. Patients were followed from initiation of antidepressant until any of the following: treatment cessation, switching, death, or loss to follow-up. The outcome is a new onset of an SRE.ResultsCitalopram exhibited a significantly fewer case with new SREs compared to other most used antidepressants such as venlafaxine, duloxetine, and mirtazapine–even after adjusting for multiple comparisons and other covariants.DiscussionFindings suggest potential risks associated with certain antidepressants in the PTSD population, emphasizing cautious prescription considerations.